EVALUASI KUALITAS LAYANAN PERPUSTAKAAN UNIVERSITAS ISLAM AS SYAFI’IYAH (UIA) - Iffah Budiningsih (Akademika : Jurnal Teknologi Pendidikan, 2016)
The purpose of this evaluation study is to know the extent to which the quality of library service – UIA inorder to support the learning process for the students of the UIA's next get what information should be improved inthe manifest ' prima ' library services. The object of this research is a student is a student of Strata program S1 in 6(six) faculty (FE, FAI, PEDAGOGY, FH, FST, FIKES) semester 7 (seven) FY 2015/2016 on The Islamic Syafi'iyahUniversity Jakarta (UIA); the number of samples of 84 students. Library service quality evaluation of variablesmeasured using instruments non test by questionnaire.The Data collected is processed and analyzed using descriptive analysis , i.e., Using a central tendency:size: mean, median, mode and size dispersion: score the minimum, maximum, standard deviation score. Theanalysis of statistical data is done with the help of program Excels and 11.5 version SPSS for windowsThe results of research on the quality evaluation of UIA library services can be explained that the average(mean) library service quality score achieved score 59.67 included in categories of